(untitled) (Vietnam Journal of Community Medicine, 2024)
Introduction: Patient experience during service use is one of the important factors that enhance the quality of the services. Objectives: This study was conducted to assess the current outpatient experiences with magnetic resonance imaging (MRI) services and its associated factors in Vinmec Nha Trang International Hospital in 2023. Methods: We applied a cross-sectional design to perform self-administered interviews with 185 outpatients in Vinmec Nha Trang International Hospital during May-June, 2023. Results: 77.9% of outpatients had a positive assessment of the MRI services. The two aspects that outpatients have the lowest rate of positive assessments are the Experience of performing MRI (53.4%) and the Experience of communication skills of health workers (74.6%). The four remaining aspects of the experience have a high rate of positive assessment ranging from 80-88%. 91.4% of outpatients reported that they could come back to re-use the services if needed. Regarding associated factors, having health insurance and used MRI services were positively related to experiences with MRI services. Conclusions: Outpatients had a high rate of positive assessment of the MRI services. Our study recommends improving the consultancy and patient support before and after performing MRI.